Rehospitalization and “Revolving Door” in Anorexia Nervosa: Are There Any Predictors of Time to Readmission? - Marzola, Enrica; Longo, Paola; Sardella, Federica; Delsedime, Nadia; Abbate-Daga, Giovanni (Frontiers in Psychiatry, 2021)
Objective: Anorexia nervosa (AN) is a severe psychiatric illness with multifactorial etiology and unsatisfactory treatment outcomes. Hospitalization is required for a substantial number of patients and readmission (RA) commonly occurs. Some individuals need multiple hospitalizations sometimes over a short amount of time thus delineating the “revolving door” (RD) phenomenon. However, very little is known about readmissions and their frequency in AN. Therefore, we aimed to longitudinally investigate readmissions in AN in order to: a) characterize patients with AN who need readmission (i.e., RA-AN), sometimes rapidly (RD-AN); b) ascertain differences between RA-AN and non-RA-AN groups during baseline hospitalization; c) investigate as to whether clinical or psychometric parameters worsened on RA; d) analyze predictors of time-to-readmission in AN. Methods: a total of 170 inpatients with AN were enrolled at their baseline hospitalization; all their subsequent rehospitalizations were recorded with a longitudinal design by which each patient has been observed for 3 years. Patients were classified as RD-AN if requiring a readmission <12 months since last discharge. Clinical characteristics were measured upon admission and discharge for each hospitalization, and, at all time points, patients completed questionnaires assessing eating and general psychopathology, and body shape concerns. Results: sixty-seven patients (39.4%) needed at least one readmission and 62 (92.5% of RA-AN) reported RD. Compared to non-RA-AN, those with RA-AN were younger, reported a shorter duration of illness, and were more frequently diagnosed with AN-BP. Also, greater severity of anxious and depressive symptoms and body shape concerns emerged in the RA-AN group. The outcome of baseline hospitalization did not differ between groups and only depressive symptoms worsened at readmission. Shorter duration of AN and low weight gain during baseline hospitalization predicted early readmission but did not survive statistical control. In contrast, high scores on drive for thinness upon baseline hospital entry robustly predicted a shorter time to readmission even after statistical control. Discussion: Individuals with AN who require readmission do so over a short period notwithstanding a positive treatment outcome during their baseline hospitalization. Shorter time-to-readmission can be predicted mostly in case of marked drive for thinness and poor weight gain at baseline hospital admission.